Analysis of Tourism Activity in the Dnipro Region in the Context of Tourism Development in Frontline Regions - Пацюк, Вікторія; Рейманн, Март; Казаков, Володимир (Київський національний університет імені Тараса Шевченка, 2024)
Although the frontline regions of eastern and northern Ukraine had significant tourism potential, tourism in these areas has not developed sufficiently, not because of a lack of resources, but because of its underestimation and incorrect positioning. The war, on the one hand, caused significant damage to the natural resources and cultural and historical monuments of these regions, and on the other hand, it drew the attention of not only Ukrainians but also the whole world to these territories.  In the future, these regions may become a springboard for the reconstruction of the territory and the development of tourism activities in accordance with all European canons and standards. The article presents the results of a Ukrainian-Estonian research project aimed at studying the development of Ukrainian frontline communities and tourism businesses in the context of war and identifying their strategies for the future. The survey was conducted in Dnipro, Sumy, Kharkiv regions and government-controlled frontline communities in Zaporizhzhia and Donetsk regions. This study focuses on comparing the peculiarities of tourism development in the frontline regions and separately in the Dnipro region both in the pre-war period and the period of active military confrontation. The focus is on the main types of tourism that were in demand before the war and those that are expected to be most in demand in the future. The author analyses the changes that occurred in tourism activities since the outbreak of the war and the problems that had to be faced in organising tourism activities after its beginning. Threats, problems, opportunities and prospects for the development of tourism in the post-war period are identified.

Прифронтові регіони сходу та півночі України хоча й мали значний туристичний потенціал, однак туризм на даних територіях розвивався недостатньо не через відсутність ресурсу, а з причин недооцінки та невірного його позиціонування. Війна, з одного боку, завдала значних збитків природним багатствам та культурно-історичним пам’яткам даних регіонів, з іншого – привернула увагу не лише мешканців України, а й всього світу до цих територій. У майбутньому прифронтові області можуть стати плацдармом для відбудови територій та розвитку туристичної діяльності за всіма європейськими стандартами. У статті презентовано результати дослідження україно-естонського науково-дослідного проєкту, що мав за мету дослідити розвиток українських прифронтових громад і туристичного бізнесу в умовах війни та виявити їх стратегії на майбутнє. Дане опитування проводилось у Дніпропетровській, Сумській, Харківській областях та підконтрольних прифронтових громадах Запорізької та Донецької областей. У даному дослідженні було сфокусовано увагу на співставленні особливостей розвитку туризму в прифронтових областях та окремо у Дніпропетровській області у довоєнний час та період активного військового протистояння. Акцентовано увагу на основних видах туризму, які користувались попитом до війни та тих видах, які за очікуваннями будуть найбільш затребуваними в майбутньому. Проаналізовано, які зміни відбулися у туристичній сфері із початком війни, та з якими проблемами довелося зіткнутися при організації туристичної діяльності після її початку. Виявлено загрози, проблеми, можливості та перспективи розвитку туристичної діяльності у повоєнний період.
Аналіз туристичної діяльності Дніпропетровщини в контексті розвитку туризму прифронтових регіонів
Keywords: tourism; frontline regions; tourist activity; survey; post-war reconstruction; Dnipro region; туризм; прифронтові регіони; туристична діяльність; опитування; повоєнна відбудова; Дніпропетровська область